Effect of areca nut extracts on growth performance, slaughtering performance, and meat quality of broiler chickens - Xu, Juan; Li, Mengyao; Li, Rong; Zhang, Zhen; Ma, Ying; Tao, Ran; Zou, Lirui; Wang, Ji; Wen, Lixin; Li, Rongfang (Frontiers in Veterinary Science, 2025)
IntroductionSince the comprehensive ban on the addition of antibiotics to livestock and poultry feeds in China, the search for safe and natural antibiotic substitutes has become a hot spot in the animal breeding industry. Areca catechu L (AN), known as the leader among the four southern medicinal herbs, possesses functions such as insecticidal, antibacterial, antiinflammatory, promoting gastrointestinal motility and preventing Alzheimer's disease. Nevertheless, ANE is rarely used as a feed additive in AA broilers, and its specific role remains unclear. This study was conducted to investigate the effects of different levels of areca nut extracts (ANE) on growth performance, slaughter performance and meat quality of AA broiler chickens.Methods128 one-day-old Arbor Acres broilers were randomly divided into eight groups of 16 birds each, housed in three cages with 5-6 birds per cage, with or without ANE supplementation (0, 100, 150, 200, 250, 300, 350, and 400 mg/kg, respectively).ResultsThe entire experiment duration was 49 days. Adding 100 and 200 mg/kg ANE to the diet could significantly increase the body weight of broilers at 21 days of age (P ≤ 0.001), and significantly reduce the feed-to-weight ratio from 1 to 21 days of age (P ≤ 0.001). The diet supplemented with 200 mg/kg ANE could significantly increase the average body weight at 49 days of age (P = 0.001). Compared with the control group, the addition of different dosages of ANE in the feed could improve the pH45min, yellowness, and shear force (P ≤ 0.043) of the pectoral and leg muscles of broilers. Additionally, the contents of crude fat and crude protein, which are nutritional components in the pectoral and leg muscles of the ANE-supplemented groups, were to an extent higher than those of the control group (P ≤ 0.036). The addition of different levels of ANE in the diet significantly raised the expression levels of muscle development-related genes, including Myf5, Myf6, MyoD1, IGF-1, and IGF-2 (P ≤ 0.032).DiscussionIn conclusion, An appropriate amount of ANE in the diet has been demonstrated to boost the growth performance and meat quality of broilers, facilitate muscle development, and has no remarkable influence on slaughter performance. the ideal dosage for broilers is 100–200 mg/kg ANE. The findings of this study offer valuable insights into the potential benefits of ANE in poultry production, and provide a basis for further research into the development of ANE as a new feed additive.